ПІСЛЯІН’ЄКЦІЙНІ ГНІЙНІ ЗАХВОРЮВАННЯ: СТАН ПИТАННЯ ТА ХІРУРГІЧНЕ ЛІКУВАННЯ - Хіміч, С. Д.; Превар, А. П.; Рауцкіс, В. П.; Кателян, О. В.; Фуніков, А. В.; Кривонос, М. І. (Українські медичні вісті, 2023)
ПІСЛЯІН’ЄКЦІЙНІ ГНІЙНІ ЗАХВОРЮВАННЯ: СТАН ПИТАННЯ ТА ХІРУРГІЧНЕ ЛІКУВАННЯ